HUBUNGAN FAKTOR PREDISPOSISI MASYARAKAT DENGAN PENGGUNAAN JAMBAN SEHAT DI LINGKUNGAN XII KELURAHAN BELAWAN I KECAMATAN MEDAN BELAWAN TAHUN 2024 - Daeli, Yolanda Mercy Rawati; Manurung, Jasmen (TOUR HEALTH JOURNAL, 2024)
Background: Healthy latrines are a basic sanitation facility to maintain environmental welfare in order to improve the degree of public health. In the XII neighborhood many people still use pour-flush latrines, although some have switched to gooseneck latrines because the majority of households are located on land. Some respondents who have adopted gooseneck latrines still dispose of feces directly to the sea, due to financial constraints, unfavorable geographical conditions and lack of environmental support for the construction of septic tanks. Purpose: This study aims to analyze the relationship between community predisposing factors and the use of healthy latrines in Neighborhood XII of Belawan I Urban Village, Medan Belawan Sub-district. Method: The type of research is quantitative with cross sectional research design. The population was all 655 families with a sample size of 87 families taken by simple random sampling. Primary data collection was done by interview and questionnaire. Data processing was done by editing, coding, data entry, cleaning and tabulating. Bivariate analysis used chi-square test with 95% confidence level (α = 0.05). Disscusion and Conclusion: The results showed that all independent variables consisting of: knowledge, economic status, attitude and education have a relationship with the use of latrines, it is necessary to make various efforts through the role of the community and health workers in improving the quality of sanitation and environmental health in Neighborhood XII Belawan I Village, Medan Belawan Subdistrict.